1999
DOI: 10.1136/oem.56.12.793
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear industry family study: methods and description of a United Kingdom study linking occupational information held by employers to reproduction and child health

Abstract: Objectives-To describe the methods used in the nuclear industry family study for which a comprehensive database has been assembled that links employment in the nuclear industry and dosimetry records to information on employees' reproductive health and the health of their children. To discuss the response rates and characteristics of the study population. Methods-Occupational cohort design leading to a retrospective cohort study of reproductive outcomes reported by 46 396 current and former employees of both se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As in previous studies [13-15] the method was found to be feasible and enabled collection of a considerable amount of information on a range of different reproductive outcomes. However the study did have a fairly low response rate and the issue of selection (responder) bias needs to be addressed.…”
Section: Discussionmentioning
confidence: 83%
“…As in previous studies [13-15] the method was found to be feasible and enabled collection of a considerable amount of information on a range of different reproductive outcomes. However the study did have a fairly low response rate and the issue of selection (responder) bias needs to be addressed.…”
Section: Discussionmentioning
confidence: 83%
“…Workers who had at least one such radiation record are referred to in this study as “monitored workers”. Natural background radiation was excluded and appropriate adjustments were made for factors such as the minimum detection dose value (threshold dose) of the dosimeter and for missing badges 10. Also, employees who are potentially exposed to radioactive substances are investigated for possible internal contamination.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…Also, employees who are potentially exposed to radioactive substances are investigated for possible internal contamination. The type of information provided on this internal monitoring varied between authorities, but all employers provided the calendar year in which an employee was monitored for the first time for potential internal contamination by any radionuclide 10. All workers for whom such a date existed are referred to in this study as internally monitored workers.…”
Section: Participants and Methodsmentioning
confidence: 99%